Dietary and Reproductive Responses of Arctic Foxes to Changes in Small Rodent Abundance - Strand, Olav; Linnell, John D.C.; Krogstad, Steinar; Landa, Arild (ARCTIC, 1999)
Between 1988 and 1995, dens in three adjacent arctic fox (Alopex lagopus) territories were monitored in an alpine environment in south-central Norway (the Snøhetta plateau). A total of 675 scats were collected at dens in both winter and summer, and the numbers of resident adults and pups at emergence were counted each summer. Small rodents (mainly Lemmus sp. and Microtus sp.) were the most frequently consumed prey and made up the greatest volume within scats, in all seasons and at all stages of the rodent cycle. Small rodents were followed in frequency by reindeer (Rangifer tarandus), hares (Lepus timidus), birds, and vegetation. Birds and vegetation were more common in the summer diet than in the winter diet, reflecting their seasonal availability. The relative volume of reindeer and birds in the diet decreased with increasing rodent abundance. Increased pup production was associated with years of high rodent abundance and a high occurrence of rodents in the diet. Adult numbers were not associated with rodent abundance. Entre 1988 et 1995, on a observé les terriers du renard arctique (Alopex lagopus), dans trois territoires contigus situés dans un environnement alpin du centre-sud de la Norvège (le plateau Snøhetta). En hiver et en été, on a recueilli un total de 675 excréments sur le site des terriers, et chaque été, on a compté le nombre de résidents adultes et de petits qui faisaient leur première sortie du terrier. Les petits rongeurs (surtout Lemmus sp. et Microtus sp.) étaient la proie la plus fréquemment consommée et constituaient le plus gros volume des excréments, en toute saison et à toute étape de la vie du rongeur. Les petits rongeurs étaient suivis en fréquence par le renne (Rangifer tarandus), le lièvre (Lepus timidus), les oiseaux et la végétation. Les oiseaux et les plantes étaient plus courants dans le régime alimentaire estival que dans celui hivernal, ce qui reflétait la disponibilité saisonnière. Le volume relatif de renne et d'oiseaux dans l'alimentation diminuait avec l'augmentation de ...